Origin of performance enhancement of superconducting nanowire single-photon detectors by He-ion irradiation - Stefan Strohauer; Fabian Wietschorke; Markus Döblinger; Christian Schmid; Stefanie Grotowski; Lucio Zugliani; Björn Jonas; Kai Müller; Jonathan J. Finley (APL Quantum)
Superconducting nanowire single-photon detectors (SNSPDs) are indispensable in fields such as quantum science and technology, astronomy, and biomedical imaging, where high detection efficiency, low dark count rates, and high timing accuracy are required. Recently, helium (He) ion irradiation was shown to be a promising method to enhance SNSPD performance. Here, we study how changes in the underlying superconducting NbTiN film and the SiO2/Si substrate affect device performance. While irradiated and unirradiated NbTiN films show similar crystallinity, we observe He bubble formation below the SiO2/Si interface and an amorphization of the Si substrate. Both reduce the thermal conductance between the superconducting thin film and the substrate from 210 to 70 W m−2 K−4 after irradiation with 2000 ions nm−2. This effect, combined with the lateral straggle of He ions in the substrate, allows the modification of the superconductor-to-substrate thermal conductance of an SNSPD by selectively irradiating only the regions around the nanowire. With this approach, we achieved a broader bias current range (9.8 μA vs 3.7 µA) in which the detector operates at its maximum detection efficiency, which is beneficial for reducing dark counts while maintaining high sensitivity. Moreover, the photon-assisted critical current remained similar to that of the unirradiated reference device (59.0 µA vs 60.1 µA), while full irradiation reduced it to 22.4 µA. Our results suggest that the irradiation-induced reduction of the thermal conductance significantly enhances SNSPD sensitivity, offering a novel approach to locally engineer substrate properties for improved detector performance.